Problems with Pupils' Reading and Solutions/مشاكل القراءة لدى التلاميذ وحلولها - Jazil Ar-Rahman (Nurul Jadid University, 2018)
Reading is a key factor in building personality and refining it. It provides the reader with the knowledge and experience that he may not be able to acquire directly through reading. It is also the tool of the student in acquiring his academic sciences and expanding knowledge horizons.